2009
DOI: 10.1139/t09-026
|View full text |Cite
|
Sign up to set email alerts
|

Measuring shear and compression wave velocities of soil using bender–extender elements

Abstract: Piezoceramic elements have been used for laboratory measurement of wave velocity in soil and rock specimens. Shear-wave piezoceramic elements (bender elements) are commonly used to measure shear wave velocity for the determination of small-strain shear modulus. Compression-wave piezoceramic elements (extender elements), on the other hand, are less commonly used as compression wave velocity is less frequently measured. In this paper, the performance of a pair of bender–extender elements for the determination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(63 citation statements)
references
References 17 publications
2
51
1
9
Order By: Relevance
“…This can either be accessed by visual inspection or using an automated procedure that detects small changes in the amplitude of the received signal for cases where visual inspection is difficult (e.g. Leong et al, 2009). In this study it was found that the arrival of the compressional wave is relatively independent of the testing frequency, although the wave propagation mode seems to change for lower excitation frequencies (i.e.…”
Section: Extension Deflectionmentioning
confidence: 67%
“…This can either be accessed by visual inspection or using an automated procedure that detects small changes in the amplitude of the received signal for cases where visual inspection is difficult (e.g. Leong et al, 2009). In this study it was found that the arrival of the compressional wave is relatively independent of the testing frequency, although the wave propagation mode seems to change for lower excitation frequencies (i.e.…”
Section: Extension Deflectionmentioning
confidence: 67%
“…Over the years, bender elements have become increasingly popular in order to determine the S-wave velocity [9,10] through experiments. Nowadays, they are commonly available [11,12].…”
Section: (1 )mentioning
confidence: 99%
“…Because of this fact, it acts as a signal transmitter. Being subjected to mechanical excitation causes the emission of an electrical output by another bender element, which is, in this way, acting as a signal receiver [9].…”
Section: (1 )mentioning
confidence: 99%
See 1 more Smart Citation
“…The most common techniques are measuring the time between the onset of the sender driving signal and detecting the first arrival at the receiver element (visual picking), travel time between two receivers some distance apart along the ray path detecting the same seismic event, as well as cross-correlation and cross-power spectrum methods (Leong et al 2005). For this project, the method of visual picking of the first arrival was used.…”
Section: Small-strain Stiffness Datamentioning
confidence: 99%